Evaluation of the Levetiracetam treatment on reduction of epileptic discharges in electroencephalogram in children with epilepsy. - Fayyazi, Afshin; Ebrahimi, Mohammad Hossein; Roshanaei, Ghodratollah; bazmamoun, hassan (Iranian Journal of Child Neurology, 2021)
Abstract: Objectives: Epilepsy is a relatively common disease in childhood. In some patients, despite clinical control of seizures, the electroencephalogram (EEG) is clearly abnormal. In some studies, the adverse effects of epileptic discharges on cognition, learning, behavior, and seizure recurrence in children have been identified. In this study, the effect of Levetiracetam on epileptic discharges in the interictal phase of EEG in children with epilepsy was investigated. Materials and Methods: In this clinical trial, 59 children aged 2 to 15 years with epilepsy, whose clinical seizures were controlled by sodium valproate in the last six months, but they still had epileptic discharges in the EEG, were randomly divided into two groups. Intervention group (24 people), whom Levetiracetam was added to sodium valproate, and control group, whom treatment with sodium valproate (35 people) alone was continued, then the patients were followed for one year. Results: The frequency of normalization of epileptic discharges in the intervention and control group was 66.7% and 57.1% (P = 0.500), respectively. The mean time for normalization of epileptic discharges in the interictal phase was 14.55%±14.31% months in the intervention group and 12.50%±20.18% months in the control group (P = 0.033). Conclusion: In children with controlled seizures whose EEG was still abnormal, both sodium valproate therapy alone and sodium valproate combined with Levetiracetam were effective in reducing the severity of epileptic discharges. But addition of Levetiracetam to sodium valproate normalizes EEG more rapidly.